2012
DOI: 10.1007/s00424-012-1121-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the hepatocyte rough endoplasmic reticulum single chloride channel by nucleotide–Mg2+ interaction

Abstract: The effect of nucleotides on single chloride channels derived from rat hepatocyte rough endoplasmic reticulum vesicles incorporated into bilayer lipid membrane was investigated. The single chloride channel currents were measured in 200/50 mmol/l KCl cis/trans solutions. Adding 2.5 mM adenosine triphosphate (ATP) and adenosine diphosphate (ADP) did not influence channel activity. However, MgATP addition inhibited the chloride channels by decreasing the channel open probability (Po) and current amplitude, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…But if this was their only role, then why does the SR contain so many different types of anion channel? An interesting report of a Cl − channel from liver rough ER that was activated by Mg 2+ -ADP and inhibited by Mg 2+ -ATP, suggested that this Cl − channel could be activated by metabolic stress (Ashrafpour et al 2012). The need for further study in this area is obvious and it must begin with identification of the proteins that constitute the SR Cl − channels so that structure-function studies can begin.…”
Section: Anion Channels Of the Er/sr And Their Multiple Mechanisms Ofmentioning
confidence: 99%
“…But if this was their only role, then why does the SR contain so many different types of anion channel? An interesting report of a Cl − channel from liver rough ER that was activated by Mg 2+ -ADP and inhibited by Mg 2+ -ATP, suggested that this Cl − channel could be activated by metabolic stress (Ashrafpour et al 2012). The need for further study in this area is obvious and it must begin with identification of the proteins that constitute the SR Cl − channels so that structure-function studies can begin.…”
Section: Anion Channels Of the Er/sr And Their Multiple Mechanisms Ofmentioning
confidence: 99%